Nasal and vaginal colonization of methicillin-resistant Staphylococcus aureus in pregnant women in Cartagena, Colombia (Colombia Medica, 2012)
Introduction: The host niche for Staphylococcus aureus (SA) are the anterior nares; however, vaginal colonization rates between 14% and 17.1% in pregnant women have been recently reported, raising interest about the potential risk in postpartum women and in neonates from colonized mothers.Objectives: To determine the prevalence of nasal and vaginal colonization of SA and the antibiotic susceptibility of the isolates in pregnant women attending a maternity hospital in Cartagena, Colombia.Methods: Nasal and vaginal swabs were obtained from participants and subjected to microbiological and molecular assays. A post discharge follow-up was performed for up to four weeks.Results: From 100 pregnant women enrolled in the study, 34 were colonized with SA; 29 only in the nares, three only in the vagina, and two at both sites. Colonization of pregnant women with SA was more common in the nares than in the vagina or at both sites [29/34 (85.3%) vs 3/34 (8.8%) and 2/34 (5.9%); p